Historical Learning of Psychological Warfare in the Jugun Ianfu System: A Case Study Based on Daugherty’s Theory and Students’ Historical Empathy - Harun, Yessy; Juliansyah, Juliansyah; Hargo, Hargo; Martia, Tia; Ananda Noviani, Aisyah (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study analyzes the psychological warfare strategies employed by the Japanese military in the forced recruitment of Jugun Ianfu during World War II in Java, Indonesia. Using William E. Daugherty’s framework, it examines propaganda, coercion, and ideological manipulation in Banten Bay, Indramayu, and Kragan, and explores their implications for fostering students’ historical empathy. Method: A qualitative historical case study approach was adopted. Data were collected from historical archives, survivor testimonies, military records, and secondary sources, and analyzed thematically using Daugherty’s psychological warfare model. Results: The findings reveal four systematic stages of psychological warfare: deceptive recruitment promises, ideological normalization through imperial doctrines, collaboration with local intermediaries, and sustained trauma reinforced by sexual violence and social stigma. These mechanisms demonstrate that the Jugun Ianfu system functioned as a structured strategy of domination with long-term psychological consequences for survivors. Novelty: This study integrates psychological warfare theory with survivor-centered historiography and history education. It highlights how analyzing wartime sexual violence through a structured theoretical framework can support the development of students’ historical empathy and ethical historical consciousness.